2016
DOI: 10.1038/ncomms13031
|View full text |Cite
|
Sign up to set email alerts
|

Mutually exclusive sense–antisense transcription at FLC facilitates environmentally induced gene repression

Abstract: Antisense transcription through genic regions is pervasive in most genomes; however, its functional significance is still unclear. We are studying the role of antisense transcripts (COOLAIR) in the cold-induced, epigenetic silencing of Arabidopsis FLOWERING LOCUS C (FLC), a regulator of the transition to reproduction. Here we use single-molecule RNA FISH to address the mechanistic relationship of FLC and COOLAIR transcription at the cellular level. We demonstrate that while sense and antisense transcripts can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
118
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(133 citation statements)
references
References 28 publications
12
118
3
Order By: Relevance
“…Thus, it has been hypothesized that the antisense transcript COOLAIR acts in cis. Indeed, recent singlemolecule RNA FISH showed that COOLAIR and FLC sense transcription is mutually exclusive and confirmed that COOLAIR acts in cis to silence FLC during cold (32). Comparison of the A. thaliana and Arabidopsis alpina FLC antisense promoter regions revealed DNA sequence conservation, and an analogous antisense transcript was also detected in the latter species (33).…”
Section: Significancementioning
confidence: 89%
See 1 more Smart Citation
“…Thus, it has been hypothesized that the antisense transcript COOLAIR acts in cis. Indeed, recent singlemolecule RNA FISH showed that COOLAIR and FLC sense transcription is mutually exclusive and confirmed that COOLAIR acts in cis to silence FLC during cold (32). Comparison of the A. thaliana and Arabidopsis alpina FLC antisense promoter regions revealed DNA sequence conservation, and an analogous antisense transcript was also detected in the latter species (33).…”
Section: Significancementioning
confidence: 89%
“…Examples of cis-acting antisense mechanisms include Xist-mediated allele-specific X-chromosome inactivation in humans and PHO gene regulation in yeast (54,55). In addition, it has been suggested that in plants the antisense transcript COOLAIR acts via the process of its transcription or by formation of an RNA cloud, as seen in single-molecule FISH suppressing FLC transcription in cis (22,32).…”
Section: Dog1 Antisense Is a Suppressor Of Seed Dormancy In Arabidopsismentioning
confidence: 99%
“…Our research suggests that the cryptic lncRNA component in such cascades could be identified by transcript profiling in nuclear exosome mutants. The lncRNA-mediated effects of long-term cold exposure on plant gene expression have been well characterized for the FLC gene 2,40 . Our research demonstrates that lncRNAs also mediate the response to short-term and transient cold exposure by timing maximal gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…To date we have used the tool, and its nascent precursors, on over fifteen internal projects at various stages of the publication pipeline (Berry et al, 2015; Duncan et al, 2016; Rosa, Duncan & Dean, 2016). As the package has matured, we have found substantial gains in our productivity.…”
Section: Resultsmentioning
confidence: 99%